Early grade scripted lesson plans (SLPs) : Responding to the International Technical Guidance For Sexuality Education (ITGSE) - Venketsamy, Thungavel (Roy) (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2021.